KUFRI KHYATI: A NEW EARLY MATURING POTATO VARIETY FOR INDIAN PLAINS - Kumar, Raj; Kang, G. S.; Pandey, S. K.; Gopal, J. (Potato Journal, 2013)
Kufri Khyati is a high yielding early maturing white tuber variety having moderate resistance to late blight and is for cultivation in plains of India. At most of the places, Kufri Khyati yielded higher than the other early maturing cultivars. An important feature of this variety is that, unlike most of the early maturing varieties, it possesses moderate resistance to late blight. This variety performs well both under very early (60 days) and early (75 days) harvests. Specific areas for its adaptation are Rajasthan, Haryana, Punjab, Uttar Pradesh, Bihar, West Bengal, Gujarat, Madhya Pradesh, Orissa and Chhatisgarh. This variety is likely to be a good replacement for early maturing cultivars Kufri Chandramukhi, Kufri Jawahar, Kufri Ashoka and Kufri Pukhraj.